Ritonavir May Prolong Sedation but is Unlikely to Increase the Risk of Respiratory Arrest in Patients Requiring Intravenous Midazolam for Procedural Sedation - Arsanious, Jason; Rowland, Angela; Sorich, Michael J; Hopkins, Ashley M; Alfred, Sam; Rowland, Andrew (Journal of clinical pharmacology, 2025)
Intravenous midazolam is frequently used for procedural sedation. Use of ritonavir containing antivirals in patients requiring procedural sedation with intravenous midazolam is postulated to increase the risk or prolong the consequences of exposure related adverse events. The primary objective of this study was to characterize interaction of ritonavir with IV midazolam. The secondary objective was to define the time course over with the interaction of ritonavir with IV midazolam resolves following cessation of ritonavir. Physiologically based pharmacokinetic modeling was used to conduct clinical trials with a parallel group design defining exposure to a single 5 mg IV dose of midazolam in the presence and absence of nirmatrelvir/ritonavir dosed twice daily for 5 days. Simulations comprised 50 virtual healthy subjects aged 20 to 50 years (50% female). Based on FDA criteria, a moderate/strong interaction between nirmatrelvir/ritonavir and intravenous midazolam (area under the curve [AUC] ratio >2) was observed when intravenous midazolam was administered up to 72 h following cessation of nirmatrelvir/ritonavir. The geometric mean (90% CI) midazolam AUC ratio was 9.21 (5.44 to 16.43) when coadministered on the final day of nirmatrelvir/ritonavir dosing. Importantly, there was no change in peak exposure; the geometric mean (90% CI) midazolam maximum concentration ratio was 0.99 (0.99 to 1.00). Use of ritonavir containing antivirals is unlikely to increase a patient's risk of experiencing an exposure related adverse event following administration of intravenous midazolam but may prolong complications in patients who experience an event. A meaningful interaction persists for 72 h following cessation of nirmatrelvir/ritonavir.